Pengaruh Adaptasi Sosial Dan Dukungan Sosial Terhadap Culture Shock Mahasiswa Rantau Nias Di Uhn Medan - Gulo, Ellenvis; Siagian, Nalom; Tobing, Artha Lumban (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study aims to analyze the influence of social adaptation and social support on culture shock experienced by Nias migrant students at HKBP Nommensen University Medan. The research employs a quantitative method with an explanatory approach. The sample consists of 82 students selected using a simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that social adaptation has a significant negative effect on culture shock, meaning that better social adaptation leads to lower levels of culture shock. Social support also has a significant negative effect on culture shock, showing that higher social support reduces culture shock levels. Simultaneously, social adaptation and social support significantly influence culture shock among Nias migrant students. This study is expected to provide insights for migrant students and educational institutions in supporting students' social adaptation processes.